Controle biológico pós-colheita da antracnose em maracujazeiro amarelo (Passiflora edulis F. flavicarpa) - Araújo, Andrezza Klyvia Oliveira de (2015)
The objective of this work was to determine the effect of biotic agents Saccharomyces cerevisiae and Trichoderma asperellum, the quality of yellow passion fruit (Passiflora edulis f. Flavicarpa) and disease severity in passion flower leaves highlighted, as well as growth of the pathogen mycelia in vitro. The treatments were sterilized distilled water - ADE (T1); 4 concentrations of commercial product based on S. serevisiae in proportion to 5; 10, 15 and 20 g / L (T2, T3, T4, T5 respectively); T. asperellum 4 concentrations at 5; 10, 15 and 20 g / L (T6, T7, T8, T9 respectively) and fungicide Mancozeb at 2.0 g / L. For quality post-harvest were evaluated variables Content of Total Soluble solids, pH, titratable acidity, area under disease progress curve (AUDPC), mycelial growth inhibition and average diameter of lesions in detached leaves. The application of treatments on fruit occurred by immersion in solutions for 2 minutes and further drying at a temperature of 25 ± 2 °C. The fruits were placed in plastic trays and subjected to a moist chamber for 24 hours. The inoculation of C. gloeosporioides occurred by depositing 7 mm fungal culture with seven days, on surface area, previously wounded, on three equidistant locations. To evaluate the mycelia growth, pure colonies were used, with 7-day-old incubated in PDA medium plus treatments. For the assessment of disease reduction in detached leaves passionflower used three leaf discs of approximately 7 cm in diameter, sprayed with suspension C. gloeosporioides spores at a concentration of 1x105 esporos.mL-1 deposited on plates Petri. It was determined the latency period through daily monitoring to identify the emergence of the first signs and symptoms of the pathogen. The results showed that the treatments did not influence the postharvest quality of passion fruit. Biological control with S. cerevisiae and T. asperellum. reduced the severity of disease in treated fruits to 20 g / L and mancozeb fungicide. For mycelial growth of the pathogen in vitro best culture conditions were 15 and 20 g /L and fungicide where the inhibition of mycelia growth was over 90% for all three treatments. For AUDPC in detached leaves, the most promising results were with S. cerevisiae and T. asperellum at 20 g / L, providing lower severity of disease.